Examining the impact of school culture on the perception of education for the school surrounding community. A case study of leadership practices in a rural non- profit school in Giza, Egypt - Hussein, Noha Nagy (AUC Knowledge Fountain, 2020)
This research investigates the impact of school culture, produced by a servant leader, on the perceptions of the parents in the rural community. The research setting is a nonprofit school in a rural community that was established for a group of marginalized people. The study examined the relationships between the leadership style and the school culture in the observed setting. It further investigated the impact of the school culture on the perceptions of the community members concerning education. The participants of this work were educational leaders, teachers, and parents in a district near Giza, Egypt. The study adopts the servant leader model in leadership as its theoretical framework; it is a qualitative study, conducted as a case study. Triangulation is used through conducting interviews, focus groups, participant observations, and examining artifacts. The final results indicate a change occurring to the perceptions of the parents, and the special featured ingredient for this change was empathy.